Recent Advances in the Synthesis of β-Ketonitriles - Kiyokawa, Kensuke; Nagata, Takaya; Minakata, Satoshi (Synthesis, 2018)
β-Ketonitriles are an important class of compounds in the field of organic and medicinal chemistry. Over the past decades, numerous efforts have been devoted to the development of new and efficient methodologies for the synthesis of these derivatives, and a number of efficient methods to accomplish this have been developed in recent years. In this context, this short review highlights recent advances in the synthesis of β-ketonitriles.1 Introduction2 Acylation of Alkyl Nitriles3 Electrophilic Cyanation of Ketone Enolates4 Electrophilic Cyanation of β-Keto Carbonyl Compounds5 Transition-Metal-Catalyzed Carbonylative Coupling Reactions6 Miscellaneous Examples7 Outlook
Keywords: ketonitriles; cyanation; acylation; carbonylative coupling; enantioselective reaction